2022
DOI: 10.1177/10664807221104191
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Seeking Behavior Among Muslims in The United States of America

Abstract: Since the 9/11 terrorist attacks, Muslims in the United States of America (MIA) have experienced increasing encounters with discrimination, hate crimes, and violence. This places them a higher risk for mental health symptoms. Although current research explores factors that impact mental health seeking behaviors of ethnic and racial minorities, there is a paucity of research examining the utilization of mental health services among religious minorities. The purpose of our study was to examine the relations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Despite experiencing sociopolitical stressors owing to their religious identity, many American Muslims still turn to religion to cope with mental health issues in addition to seeking formal treatment [9], [12], [15][16][17][18][19][20]. Research has shown that some Muslims perceive mental illness as a test from God, and Islam as a source of healing and strength [6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite experiencing sociopolitical stressors owing to their religious identity, many American Muslims still turn to religion to cope with mental health issues in addition to seeking formal treatment [9], [12], [15][16][17][18][19][20]. Research has shown that some Muslims perceive mental illness as a test from God, and Islam as a source of healing and strength [6].…”
Section: Introductionmentioning
confidence: 99%